Fortalecimento muscular na osteoartrite de joelho de ratos: implicações locais e sistêmicas - Vasilceac, Fernando Augusto (Universidade Federal de São Carlos, 2014)
Osteoarthritis is the most common disease among the elderly ostemioarticular, being of great relevance for public health and for studies related to aging processes. In this context, the muscle strengthening becomes important as a major strategy in the rehabilitation of individuals with osteoarthritis. Much research in the area have been developed, but there are few studies that have advanced the timely investigation of the effects of exercise for muscle strengthening in key local and systemic manifestations of osteoarthritis. Therefore, the aim of this thesis was to investigate the possible effects of a protocol for muscle strengthening in the main manifestations of knee osteoarthritis in rats. To achieve this goal, 3 studies were developed: Physical exercises in animal models of osteoarthritis: a literature review; Influence of muscle strengthening on knee osteoarthritis in rats according to the recommendations for the histological evaluation of OARSI (Osteoarthritis Research Society International); Effect of muscle strengthening on knee osteoarthritis biomarkers of rats. Based on our main findings, we identified the lack of studies in the area to investigate the effect of exercise on muscle strengthening animal models of osteoarthritis. This result that spurred our investigation. It was also identified that exercise muscle building became the evolution of slower disease, to a lesser extent of degeneration and cartilage damage. Finally, complementing our initial findings, muscle strengthening reduced the local expression of biomarkers such as caspase-3, metalloproteinase-1, matrix metalloproteinase-13 and interleukin-6. He also served in the systemic expression of interleukin-6, demonstrating a protective effect for biomarkers of cartilage catabolism investigated. Therefore, exercise muscle strength building has the potential to act on the principal manifestations of osteoarthritis, whether local or systemic. The application of this type of exercise with care and support in the literature, but also recommended the development of new studies that investigate the effect of muscle strengthening in other manifestations of osteoarthritis.
Keywords: Fisioterapia; Osteoartrite; Exercícios físicos; Fortalecimento muscular; Envelhecimento; Cartilagem; Aging; Osteoarthritis; Cartilage; Exercise; Muscle strengthening; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL